The Impact of ESG Listing on Firm Value in Indonesia: An Analysis Before and During the Covid-19 Pandemic - Dewantoro, Salsabila Putri; Retnawati, Anna (LP2M IAIN Palopo, 2025)
Awareness of environmental, social, and corporate governance (ESG) issues is increasing, encouraging companies to adopt sustainable practices. This study analyzes the effect of ESG listings on firm value in Indonesia, considering the periods before and during the Covid-19 pandemic. The sample consists of companies listed on the Indonesia Stock Exchange (IDX) during 2017–2023, with ESG listings measured using the SRI-KEHATI index. The results show that ESG listings have a positive effect on firm value, indicating that companies with good ESG performance tend to have higher valuations. However, the moderation results indicate that the Covid-19 pandemic did not significantly strengthen the relationship between ESG listings and company value. These findings emphasize the importance of ESG in creating value for companies, although the role of ESG in dealing with crises such as the pandemic still requires further research.